The Fine Scratches of the Spectacle Frames and the Allergic Contact Dermatitis - Kim, In Su (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2013)
BACKGROUND: Spectacle contact allergy is not infrequent. The fine scratches on the spectacle frames which may play a role in the sensitization to the potential allergenic components have not been studied. OBJECTIVE: We sought the relationship between the scratches on the spectacle frames and the allergic contact dermatitis (ACD) in the Republic of Korea. METHODS: A total of 42 Korean patients with ACD at the spectacle contact sites were enrolled. Their spectacle frames were examined with the dimethylglyoxime (DMG) test and analyzed by the scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS). Patch tests (thin-layer rapid use epicutaneous test [TRUE tests]) were performed to identify the skin allergens. RESULTS: The DMG-positive spectacle frames were identified in 78.5% of the frames. The SEM results showed that there were more scratches on the skin-contacting parts of the spectacle frames than the non-skin-contacting parts of the same frames. In the EDS findings, the mean nickel content (weight, %) of the spectacle frames was 15.7±5.5, and the mean chromium content was 20.3±3.4 at the skin-contacting parts. In the TRUE tests, nickel sulphate was the most common allergen (31 cases, 73.8%), and potassium dichromate was the second (9 cases, 21.4%). Three patients presented simultaneous positive reactions with nickel sulphate and potassium dichromate. CONCLUSION: Minor visible and non-visible fine scratches on the spectacle frames may present the provocation factors of the ACD. Nickel sulphate was the most common allergen suspected of provoking the spectacle frame-induced ACD, followed by potassium dichromate.